2015
DOI: 10.1186/s12985-015-0428-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined genetic variants of human cytomegalovirus envelope glycoproteins as congenital infection markers

Abstract: BackgroundHuman cytomegalovirus (HCMV) is still considered to be the main viral cause of birth defects and long-term neurological and sensory sequelae following congenital infection.Several Authors sustain a key role of HCMV envelope glycoproteins, such as gB, gN and gO - mainly involved in cell targeting, viral penetration and spread - as putative virulence factors. The genes coding for these glycoproteins possess hypervariable regions, resulting in a number of genetic variants in circulating clinical strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
(64 reference statements)
0
18
0
Order By: Relevance
“…A report by Firth et al, 2016 and Lachmann et al, 2018 also explained the higher incidence of CMV in female patients [46, 47]. Genetic polymorphisms of envelope glycoproteins among circulating CMV strains are generally considered as probable virulence indicators [48], and may be accountable for differential CMV tropism to precise cell types and differential capacity to distribute and interfere with normal tissue growth [30, 39]. Previous reports show that four gB genotypes of CMV are observed in congenital cytomegaly [48, 49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A report by Firth et al, 2016 and Lachmann et al, 2018 also explained the higher incidence of CMV in female patients [46, 47]. Genetic polymorphisms of envelope glycoproteins among circulating CMV strains are generally considered as probable virulence indicators [48], and may be accountable for differential CMV tropism to precise cell types and differential capacity to distribute and interfere with normal tissue growth [30, 39]. Previous reports show that four gB genotypes of CMV are observed in congenital cytomegaly [48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms of envelope glycoproteins among circulating CMV strains are generally considered as probable virulence indicators [48], and may be accountable for differential CMV tropism to precise cell types and differential capacity to distribute and interfere with normal tissue growth [30, 39]. Previous reports show that four gB genotypes of CMV are observed in congenital cytomegaly [48, 49]. Several studies reported that cCMV infections among Costa Rican, Indian and Chinese infants were caused by gB1, gB2, and gB3 genotypes [29, 42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the sequence variation of UL55 gene that encodes gB, there are four major gB genotypes(gB1, gB2, gB3, gB4) [ 10 13 ]. In addition, three nonprototypic genotypes (gB5, gB6, gB7) have been identified [ 14 ] [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Envelope glycoproteins are involved in viral entry and cell‐to‐cell virus transmission 7,8 . HCMV glycoprotein B (gB), encoded by ORF UL55, is the most widely studied envelope glycoprotein and has four main gB genotypes: gB1, gB2, gB3, and gB4 3,9‐13 . gB is a component of the envelope complex gC‐I and an important target of humoral and cellular immune responses, which is involved in virus attachment and entry, cell‐to‐cell virus transmission, and fusion of infected cells 2,7,9,14‐18 .…”
Section: Introductionmentioning
confidence: 99%